2002
DOI: 10.1046/j.1365-2257.2002.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation abnormalities associated with extensive venous malformations of the limbs: differentiation from Kasabach-Merritt syndrome

Abstract: Confusion in the nomenclature of vascular malformations has been a major obstacle to the understanding of these conditions, so that misdiagnosis and treatment inconsistencies are common. Coagulation abnormalities occurring in combination with venous malformations (VM) have been misdiagnosed as Kasabach-Merritt syndrome (KMS), despite marked differences in clinical features, pathology and treatment. A homogenous group of 24 patients with diffuse limb VM was entered into a retrospective chart review study. The V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
189
1
9

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(203 citation statements)
references
References 15 publications
4
189
1
9
Order By: Relevance
“…However, Kasabach-Merritt syndrome is a congenital hemangioma with disseminated intravascular clotting in children and is a different condition from vascular malformations with coagulopathy. 1) In the present case, the lesions developed very slowly as the patient grew, and she had no sign of right heart strain or mild symptoms of venous stasis, therefore, her disease was first considered being AVM with a small shunt volume. However, she had extensive venous enlargement which developed into serious consumptive coagulopathy due to a mechanism similar to that of venous-predominant vascular malformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Kasabach-Merritt syndrome is a congenital hemangioma with disseminated intravascular clotting in children and is a different condition from vascular malformations with coagulopathy. 1) In the present case, the lesions developed very slowly as the patient grew, and she had no sign of right heart strain or mild symptoms of venous stasis, therefore, her disease was first considered being AVM with a small shunt volume. However, she had extensive venous enlargement which developed into serious consumptive coagulopathy due to a mechanism similar to that of venous-predominant vascular malformation.…”
Section: Discussionmentioning
confidence: 99%
“…Mazoyer et al reported that a vitamin K antagonist was ineffective and advocated that permanent elastic compression with heparin therapy was the only effective treatment for LIC. 1) However, the present patient's coagulopathy improved and has been well controlled by only warfarin therapy and compression. Nevertheless, careful follow-up of possible stasis complications and coagulation disorder will be required for some time in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este trastorno, en función de la gravedad puede producir hemorragias y trombosis en situación basal y empeorar claramente con algunos tratamientos (inmovilización postquirúrgica, escleroterapia). Su estudio recomienda realizar un hemograma, donde el número de plaquetas suele estar en el límite bajo de la normalidad (distinto de la CID que se produce por atrapamiento local de plaquetas en el fenómeno de KasabachMerritt), un tiempo de protrombina, fibrinógeno (que suele estar disminuido), dímero-D (habitualmente elevado), y complejos solubles de fibrina (que suelen estar presentes) 11,12 .…”
Section: Estudio De La Coagulaciónunclassified
“…Klippel Trenaunay Syndrome must be differentiated from the Parkes-Weber syndrome [6]. Both are characterized by overgrowth limbs.…”
Section: Introductionmentioning
confidence: 99%